Nanoliter Scale Parallel Liquid–Liquid Extraction for High‐Throughput Purification on a Droplet Microarray. Issue 9 (20th December 2022) - Wiedmann, Janne J.; Demirdögen, Yelda N.; Schmidt, Stefan; Kuzina, Mariia A.; Wu, Yanchen; Wang, Fei; Nestler, Britta; Hopf, Carsten; Levkin, Pavel A.
Abstract: In the current drug discovery process, the synthesis of compound libraries is separated from biological screenings both conceptually and technologically. One of the reasons is that parallel on‐chip high‐throughput purification of synthesized compounds is still a major challenge. Here, on‐chip miniaturized high‐throughput liquid–liquid extraction in volumes down to 150 nL with efficiency comparable to or better than large‐scale extraction utilizing separation funnels is demonstrated. The method is based on automated and programmable merging of arrays of aqueous nanoliter droplets with organic droplets. Multi‐step extraction performed simultaneously or with changing conditions as well as handling of femtomoles of compounds are demonstrated. In addition, the extraction efficiency is analyzed with a fast optical readout as well as matrix‐assisted laser desorption ionization‐mass spectrometry on‐chip detection. The new massively parallel and miniaturized purification method adds another important tool to the chemBIOS concept combining chemical combinatorial synthesis with biological screenings on the same miniaturized droplet microarray platform, which will be essential to accelerate drug discovery. Abstract : Liquid–liquid extraction is widely used to separate mixtures based on their affinity to an aqueous and organic solvent, but this requires large volumes and time‐consuming handling. In this work, extraction is performed in nanoliter volumes in a miniaturized array format to enable the extraction of 192 samples at once with only two dispensing steps for the whole procedure.